2021
DOI: 10.1002/essoar.10506636.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extensive remineralization of peatland-derived dissolved organic carbon and acidification in the Sunda Shelf Sea, Southeast Asia

Abstract: Southeast Asia harbors the largest area of the world's tropical peatlands, which are widely distributed in coastal areas of Sumatra and Borneo and store around 69 Pg C of terrestrial organic carbon (Dommain et al., 2014;Page et al., 2011). Consequently, Southeast Asia is also a hotspot of terrestrial organic carbon export to the ocean: the fluvial flux of terrigenous dissolved organic carbon (tDOC) to the Sunda Shelf Sea is ∼21 Tg C yr −1 , which accounts for ∼10% of the annual global land-to-ocean tDOC flux b… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 59 publications
2
10
0
Order By: Relevance
“…In addition, Zhou et al. (2021) reported that coastal seawater containing tDOC input from Sumatra showed less than 6% loss of DOC over a 109‐day biodegradation experiment; although this study could not determine whether the DOC loss represented microbial remineralization of marine‐produced DOC or of peatland tDOC.…”
Section: Discussionmentioning
confidence: 69%
“…In addition, Zhou et al. (2021) reported that coastal seawater containing tDOC input from Sumatra showed less than 6% loss of DOC over a 109‐day biodegradation experiment; although this study could not determine whether the DOC loss represented microbial remineralization of marine‐produced DOC or of peatland tDOC.…”
Section: Discussionmentioning
confidence: 69%
“…In a separate analysis of the carbon biogeochemistry from our time series, Zhou et al (2021) showed that the stable carbon isotope composition of DOC (δ 13 C DOC ) was as low as −25.5 ‰ during the SW Monsoon, which can only be explained by tDOC input. An isotope mass balance of dissolved organic and inorganic C showed that the riverine tDOC source during the SW Monsoon must have a mean (± SE) DOC concentration of 892 ± 104 μmol l −1 (Zhou et al 2021).…”
Section: Sources and Seasonality Of Cdommentioning
confidence: 85%
“…In a separate analysis of the carbon biogeochemistry from our time series, Zhou et al (2021) showed that the stable carbon isotope composition of DOC (δ 13 C DOC ) was as low as −25.5 ‰ during the SW Monsoon, which can only be explained by tDOC input. An isotope mass balance of dissolved organic and inorganic C showed that the riverine tDOC source during the SW Monsoon must have a mean (± SE) DOC concentration of 892 ± 104 μmol l −1 (Zhou et al 2021). This is equal to the discharge-weighted mean (± SD) DOC concentration reported by Wit et al (2018) for the 4 main peatland-draining river systems on Sumatra that are closest to our site (890 ± 159 μmol l −1 ), which demonstrates that the tDOC and the terrigenous CDOM in the Singapore Strait during the SW Monsoon must originate from these peatlands.…”
Section: Sources and Seasonality Of Cdommentioning
confidence: 85%
See 1 more Smart Citation
“…Nichols Robert Scott; Patrick Martin, 2021, "Related data for: Low biodegradability of dissolved organic matter from Southeast Asian peat-draining rivers (Nichols & Martin, 2021)," https://doi.org/10.21979/N9/0RIGHW…”
Section: Data Availability Statementmentioning
confidence: 99%